Ruokinnan vaikutus naudanlihantuotannon kannattavuuteen - Nissi, Veli-Pekka; Rinne, Marketta; Pietola, Kyösti (Maatalouden taloudellinen tutkimuslaitos, 1999)
This study compares the effects of alternative feeding ratios on the returns to beef production in Finland. The comparisons focus on the amount of industrially processed feeds, having high energy content, and quality of silage. The goal was to estimate the Marginal Value Products (MVP) for convertible energy component in the feed and digestibility of silage. The data are from the feeding experiments of the Agricultural Research Centre. Daily animal growth was the highest in the animal group having the second highest amount of industrially processed feed. This amount was 36-44 % of the dry matter of the total feed. But under the current feed and meat prices the highest net returns were obtained at the highest level of industrially processed feed in the sample (47-75 % of the dry matter). The MVP for a MJ of convertible energy was estimated at FIM 0,143. For example, the MVP for barley, a basic energy feed, is estimated at FIM 1,67, which clearly exceeds the price of barley. The result suggests that, around the amount of energy feed in the sample, it is profitable to increase energy in the feeding ratios. The marginal returns to a 1 % increase in the digestibility of silage was estimated at FIM 0,09. The value difference between the lowest quality silage and the highest quality silage in the sample was estimated at FIM 1,2. Because the production costs of silage do not substantially depend on the quality of the silage, there is potential for increasing the returns to beef production by putting effort to increasing the quality of silage.
Keywords: Ko; Ma; naudanlihantuotanto; rehut; ruokinta; kannattavuus; beef production; feeding rations; energy; digestibility of silage; marginal value products